Amitriptyline: Useful for the prophylactic treatment of migraine? (Research, Society and Development, 2022)
Migraine is a type of headache described by recurrent attacks that may be accompanied by some symptoms, such as nausea, vomiting, phonophobia, among other conditions. About 1 billion people in the world could come into existence. Some measurements are recognized for the treatment of use, as measurements are made appropriately with cost drugs. Amitriptyline has become a great alternative for the prophylactic treatment of migraine, its metabolization is extensively in the liver and its analgesic effect is linked to the ability to modulate mood or modulate the excitability of neurons that transmit pain signals from the dura mater. This study is an integrative literature review. A search key was created, and the search was performed in the Web of Science (WoS-all databases). A temporal search was carried out between the years 2018 to June 2022, without language restriction. Tools such as MapChart were used to create the worldwide distribution map based on the corresponding author. 100 articles were rescued from the Web of Science, of which only 20 were chosen to compose the final table, due to their high relevance and sensitivity in the investigated topic. Migraine prevention for patients is critical, as it can reduce stigma and enhance quality of life.